Empowering pearl lobster farmers through synbiotic feed training for disease prevention - Diana Yulanda Syahailatua; Hellen Afia Sahusilawane; Santi Penina Tua Rahantoknam; Tati Atia Ngangun (University of Merdeka Malang, 2026)
Pearl lobsters (Panulirus ornatus) are widely cultivated in coastal areas of Indonesia, including in Ohoidertom Village, Southeast Maluku. However, organism health management greatly affects lobster cultivation, especially in terms of disease prevention and treatment. The objective of the community service activity was to increase the knowledge and understanding of the Sevav Ratut Group about the prevention of pearl lobster diseases using synbiotic feed. The method used was a participatory method through presentations and hands-on practice, including the preparation, implementation, assistance, and evaluation stages. During the implementation stage, the partners directly practised making synbiotic feed from papaya leaves and yoghurt. The feed was then applied to pearl lobsters. During the socialisation and training activities, participants showed a desire to develop. This was demonstrated by their attendance, participation in discussions, and involvement in activities, from instructions on making herbal synbiotic feed to feeding it to cultivated pearl lobsters. The evaluation results showed that participants had a better understanding of the material provided. This was also supported by the active involvement of participants during the discussion sessions and the practical session on making herbal synbiotics. The average score of participants before the test was 37, while their average score after the test increased to 92. This increase indicates that the training activities can enhance participants' understanding of the concept of probiotics.